Gaudin, C., Flandin, S., Moussay, S., & Chaliès, S. (Éd.). (2018). Vidéo-formation et développement de l’activité professionnelle enseignante. - Perrin, Nicolas (Swiss Journal of Educational Research, 2019)
-